The effects of material and moral incentives on the performance of workers Case study of the "Syrian Private University" (Damascus University Journal for the economic and Political sciences, 2021)
The aim of this study was to find out the effect of material and moral incentives on the performance of employees at the Syrian Private University.The researcher used the analytical descriptive method, and the questionnaire was based on obtaining the necessary data.The researcher used the comprehensive enumeration method. The questionnaire was distributed to all the administrative staff at the university, which is (85) workers, and was restored (73) questionnaires by (85.88%), The questionnaire included (40) paragraphs in addition to the demographic information prepared by the researcher divided into five grades ranging from strongly agreed and strongly disagreeable, and then analyzed using the SPSS program.The most important results were: The level of performance of administrative staff at the Syrian Private University was high from the point of view of the respondents. Material incentives that affect staff performance are limited to "end of service benefits" and "overtime".The moral incentives that affect the level of performance of employees are limited to "thanksgiving at work", "honor at official and informal events", "invitation to attend conferences and exhibitions on the nature of the work of the university" and "invitation to attend public seminars in an official manner." Finally, there was a statistically significant effect of both material and moral incentives on the performance of university employees, where the effect of the material incentives on the performance of the workers was linear, while the variable of moral incentives affected the performance variable of the employees in reverse.The study recommended re-evaluating the system of material and moral incentives at the university so that a fair incentive policy will be put in place that includes an impact on improving the performance of employees such as bonuses, compensation and annual physical benefits associated with outstanding performance and the ideal employee for each month and appreciation and thanks to others and others.As well as work to study the needs of workers and work to motivate them by satisfying those needs that are not saturated.It also recommended the distribution of incentives in a fair and thoughtful manner that includes all employees and linking them to outstanding performance to maintain their effectiveness.Finally, clear, achievable and fair performance standards must be developed and training of personnel should be undertaken and linked to the incentive system to encourage employees to improve their performance in order to obtain them.
Keywords: The effects of material and moral incentives on the performance of workers Case study of the